#Springwatch #WildMorningswithChris: Engaging With Nature via Social Media and Wellbeing During the COVID-19 Lockdown - Xu, Shi; Murrell, George; Golding, Sarah E.; Brockett, Beth F. T.; Gatersleben, Birgitta; Scarles, Caroline; White, Emma V.; Willis, Cheryl; Wyles, Kayleigh J. (Frontiers in Psychology, 2021)
It is widely understood that nature engagement benefits human wellbeing. Such benefits have been found for real as well as virtual engagements. However, little is known about the role of nature-based videos in social media on wellbeing. With COVID-19 restrictions limiting people’s direct engagement with natural environments, this study critically examined people’s reactions to nature videos posted on Facebook during the first UK COVID-19 lockdown in 2020. Data consisted of comments on videos containing highlights from the British Broadcasting Corporation’s (BBC) Springwatch 2020 television series, and from a UK television presenter and naturalist’s (Chris Packham) livestream videos, posted on Facebook from March to July, 2020. Looking at the quantitative profile of a range of videos (i.e. views, likes and shares) and a detailed analysis of the 143,265 comments using thematic analysis, three major themes were generated as: (1) engaging with nature via social media is emotionally complicated, (2) cognitive and reflective reactions are generated from social media nature engagement and (3) engagement with nature-based social media as a mechanism for coping with stress during COVID-19. These findings inform understanding of how nature-related social media content and associated commentary have supported wellbeing throughout the ongoing pandemic and their importance as a means of continued support for wellbeing. ‘We feel that the injection of wildlife into people’s homes, particularly at this point, would be really valuable and uplifting’. — Chris Packham, 2020